Amyloid in biopsies of the gastrointestinal tract: a retrospective observational study on 542 patients - Freudenthaler, Sophie; Hegenbart, Ute; Schönland, Stefan; Behrens, Hans-Michael; Krüger, Sandra; Röcken, Christoph (Virchows Archiv, 2016)
In this retrospective observational study, we investigated the histopathological and demographic characteristics of amyloid in gastrointestinal biopsies. From the Amyloid Registry Kiel, we retrieved all cases with amyloid in biopsies of the stomach, duodenum, small intestine, large intestine, and rectum submitted for tertiary referral between January 2003 and April 2013. Amyloid was identified by Congo red staining in combination with polarization microscopy and classified by immunohistochemistry. The TTR-genotype was assessed in 56 patients. Amyloid type was correlated with demographic patient characteristics. Six hundred sixty-three biopsies from 542 patients were retrieved. Amyloid was found in each biopsy as vascular and/or interstitial amyloid deposits. Biopsies were obtained from the colon [254 biopsies (38.3 %)], stomach, [153 (23.1 %)], rectum [112 (16.9 %)], duodenum [105 (15.8 %)], and jejunum/ileum [39 (5.9 %)]. ALλ amyloid was found in 286 (52.8 %), ATTR in 88 (16.2 %), ALκ in 74 (13.7 %), AA in 58 (10.7 %), and ApoAI amyloid in 4 (0.7 %) patients. The remaining 21 cases were ALys amyloid in 4 (0.7 %), AL n.o.s. in 14 (2.6 %), and mixed type amyloidosis in 3 (0.6 %). The amyloid of 11 (2.0 %) cases remained unclassified. The median age of the patients was 68 years. Men [332 (61.7 %)] were significantly more prevalent than women [206 (38.3 %); p < 0.001]. TTR mutations were found in 24 % of the patients with ATTR amyloidosis. The median age, the histoanatomical distribution (proximal to distal; mucosal to submucosal), and the deposition pattern (vascular/interstitial) varied between different amyloid types. Amyloid in gastrointestinal biopsies mainly affects male elderly patients and shows amyloid-type-specific demographic patient characteristics.